Vitalità del negativo nell'arte italiana 1960/70 - Bonito Oliva, Achille; Argan, Giulio Carlo; Boatto, Alberto; Calvesi, Maurizio; Dorfles, Gillo; Menna, Filiberto; Vivaldi, Cesare (Firenze : Centro Di, 1970)
Agnetti, Vincento ; Alfano, Carlo ; Aiviani, Getulio ; Angeli, Franco ; Anselmo, Giovanni ; Biasi, Alberto ; Boetti, Alighiero ; Bonalumi, Agostino ; Boriani, Davide ; Castellani, Enrico ; Ceroli, Mario ; Colombo, Gianni ; De Vecchi, Gabriele ; Fabro, Luciano ; Festa, Tano ; Fioroni, Giosetta ; Kounellis, Jannis ; Lo Savio, Francesco ; Mambor, Renato ; Manzoni, Piero ; etc.
Vitalità del negativo nell'arte italiana 1960/70, Palazzo della Esposizioni, Roma, novembre 1970 / gennaio 1971
boek
Keywords: Italië